Dietary nitrate supplementation very slightly mitigates the oxidative stress induced by high-intensity training performed in normobaric hypoxia - Sousa, A.; Chambion-Diaz, M.; Pialoux, V.; Carin, R.; Viana, J. L.; Milheiro, J.; Machado Reis, V.; Millet, G. (Biology of Sport, 2025)
Oxidative stress is augmented under hypoxic environments, which may be attenuated with antioxidant supplementation. We investigated the effects of dietary nitrate (NO3-) supplementation combined with high-intensity training performed under hypoxic conditions on antioxidant/pro-oxidant balance. Thirty trained participants were assigned to one of three groups - HNO: hypoxia (13% FiO2) + NO3-; HPL: hypoxia + placebo; CON: normoxia (20.9% Fi O2) + placebo - while performing 12 cycling high-intensity interval training (HIIT) sessions during a 4-week period (3 sessions/week). Before and after the intervention, venous blood samples were collected and a time to exhaustion test (Tlim) was performed (with vastus lateralis changes in local O2 saturation: SmO2 monitoring). Glutathione peroxidase (GPX) activity increased in CON (p = 0.017, ~20%) and superoxide dismutase (SOD), catalase and ferric-reducing antioxidant power (FRAP) did not change in any group. Malondialdehydes (MDA) increased in both HNO (p = 0.001, ~60%) and CON (p = 0.023, ~30%) but not in HPL. Advanced oxidation protein products (AOPP), uric acid, and myeloperoxidase activity were not modified by the protocol. Only the CON group recovered faster after the Tlim test (SmO2recovery: p = 0.0003, ~58%). Hypoxic exposure during high-intensity training blunted the increase in GPX and MDA after the intervention period. However, the effects of NO3- supplementation seem to very slightly mitigate the detrimental effect of performing high-intensity training under hypoxic conditions.